Behavior of current distribution evolution under reactant starvation conditions based on a single polymer electrolyte membrane fuel cell (PEMFC) with triple-serpentine flow field: An experimental study. (29th April 2023) - Xia, Zhifeng; Chen, Huicui; Shan, Wanchao; Zhang, Ruirui; Zhang, Tong; Pei, Pucheng
Abstract: Reactant starvation is unfavorable to the durability and life extension of PEMFC engines. In this paper, a 25 cm 2 segmented PEMFC is assembled to investigate starvation phenomenon, and the contour maps of current distribution are given to analyze the reactant starvation mechanism. The experimental results prove the high-quality homogeneity of current with triple-serpentine configuration even under starvation conditions. The air starvation experiments suggest the migration of lowest current region and the variation trend of standard deviation with the increasing of stoichiometry. The survival time increases with the anode stoichiometry, and the current density of anode downstream constantly increases with the reversal of cell, reflecting severe hydrogen starvation in these local areas. It is concluded ORR dominates the specific current distribution rather than any other electrochemical reactions. This study sheds the light of improving the lifespan and potential large-scale commercialization realization of PEMFC engines. Graphical abstract: Image 1 Highlights: Systematical analysis on reactant starvation of PEMFC was performed. Triple-serpentine flow field exhibits excellent homogeneity of current density. The lowest current area moves downstream with the increment of air supply. Behavior of current density near the outlet closely relates to hydrogen supply. Complexity of involved reactions affects the uniformity of current distribution.